PERAN GURU DALAM PENCEGAHAN DAN PENANGANAN KEKERASAN DI LINGKUNGAN SEKOLAH DASAR-LITERATUR REVIEW - Rohmah Khasanah; Dini Rakhmawati; Arri Handayani (STKIP Subang, 2024)
Violence in the elementary school environment is a serious problem that can affect children's physical, mental and emotional development. This research aims to describe the role of teachers in preventing and handling violence in elementary schools. This research method involves a literature survey and content analysis to present a comprehensive picture of teachers' duties and responsibilities in creating a safe learning environment. The research results show that teachers have a key role in preventing violence through implementing character education programs, forming positive behavior, and developing students' social skills. In addition, teachers are responsible for detecting signs of violence, both physical and verbal, and reporting them to the authorities. In handling violence, teachers act as mediators and facilitators in resolving conflicts between students. They must also provide emotional support to victims and perpetrators, while working with school staff, parents, and other relevant parties to provide appropriate corrective action. Teachers' active involvement in training and self-development related to classroom management, effective communication, and understanding the needs and uniqueness of each student is very important. Teachers' awareness of the impact of violence on children's development and their readiness to deal with situations involving violence are important aspects in creating a safe and supportive learning environment. This research concludes that the teacher's role is not only limited to delivering lesson material, but also involves social and emotional responsibility in creating a positive and violence-free learning environment for children in elementary schools.